Dermal ultrasound measurements for bone quality assessment : An investigation of advanced glycation endproducts derived from confocal fluorescence microscopy. Issue 2 (9th May 2022) - Haffer, Henryk; Chiapparelli, Erika; Moser, Manuel; Muellner, Maximilian; Dodo, Yusuke; Adl Amini, Dominik; Zhu, Jiaqi; Miller, Theodore T.; Han, Yi Xin; Donnelly, Eve; Shue, Jennifer; Sama, Andrew A.; et al.
Abstract: Bone quality is increasingly being recognized in the assessment of fracture risk. Nonenzymatic collagen cross‐linking with the accumulation of advanced glycation end products stiffens and embrittles collagen fibers thus increasing bone fragility. Echogenicity is an ultrasound (US) parameter that provides information regarding the skin collagen structure. We hypothesized that both skin and bone collagen degrade in parallel fashion. Prospectively collected data of 110 patients undergoing posterior lumbar fusion was analyzed. Preoperative skin US measurements were performed in the lumbar region to assess dermal thickness and echogenicity. Intraoperative bone biopsies from the posterior superior iliac spine were obtained and analyzed with confocal fluorescence microscopy for fluorescent advanced glycation endproducts (fAGEs). Pearson's correlation was calculated to examine relationships between (1) US and fAGEs, and (2) age and fAGEs stratified by sex. Multivariable linear regression analysis with adjustments for age, sex, body mass index (BMI), diabetes mellitus, and hemoglobin A1c (HbA1c) was used to investigate associations between US and fAGEs. One hundred and ten patients (51.9% female, 61.6 years, BMI 29.8 kg/m 2 ) were included in the analysis. In the univariate analysis cortical and trabecular fAGEs decreased with age, but only in women (cortical: r = −0.32, p = 0.031; trabecular: r = −0.32; p = 0.031). After adjusting for age, sex, BMI, diabetes mellitus, and HbA1c, lower dermal ( β = 1.01; p = 0.012) and subcutaneous ( β = 1.01; p = 0.021) echogenicity increased with increasing cortical fAGEs and lower dermal echogenicity increased with increasing trabecular fAGEs ( β = 1.01; p = 0.021). This is the first study demonstrating significant associations between skin US measurements and in vivo bone quality parameters in lumbar fusion patients. As a noninvasive assessment tool, skin US measurements might be incorporated into future practice to investigate bone quality in spine surgery patients.